2010
DOI: 10.1109/tns.2010.2068577
|View full text |Cite
|
Sign up to set email alerts
|

Origin of Radiation Induced Damage in Organic P3HT:PCBM Based Photocells

Abstract: Organic semiconductor photocells based upon P3HT:PCBM (1:1 by weight) have been subjected to X irradiation. The carrier lifetime has been determined using a pulsed optical method with continuous light to generate an open circuit voltage bias. No effect is observed on the carrier lifetime up to 300 krad (SiO 2 ). However, changes in the open circuit voltage are observed and we argue that these result from compensation of the internal field which results from the built-in potential. The origin of the field modif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…However, unlike their crystalline solid-state counterparts, there is no one distinct junction between the two materials as they are structured as a blended heterojunction. The most common donor material for organic solar cells is the conjugated polymer poly(3-hexylthiophene) (P3HT) blended with fullerene derivative phenyl-C61-butyric acid methyl ester (PCBM) as the acceptor 41,42 . The use of P3HT:PCBM to measure 70kV x-rays has been reported within the context of their exploitation in the field of medical imaging, showing that with the aid of a NaI(Tl) or a CsI(Tl) scintillator the device response is linearly dependent on the x-ray dose rate 43 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, unlike their crystalline solid-state counterparts, there is no one distinct junction between the two materials as they are structured as a blended heterojunction. The most common donor material for organic solar cells is the conjugated polymer poly(3-hexylthiophene) (P3HT) blended with fullerene derivative phenyl-C61-butyric acid methyl ester (PCBM) as the acceptor 41,42 . The use of P3HT:PCBM to measure 70kV x-rays has been reported within the context of their exploitation in the field of medical imaging, showing that with the aid of a NaI(Tl) or a CsI(Tl) scintillator the device response is linearly dependent on the x-ray dose rate 43 .…”
Section: Introductionmentioning
confidence: 99%
“…The most common donor material for organic solar cells is the conjugated polymer poly(3hexylthiophene) (P3HT) blended with fullerene derivative phenyl-C61-butyric acid methyl ester (PCBM) as the acceptor. 41,42 The use of P3HT:PCBM to measure 70 kV x rays has been reported within the context of their exploitation in the field of medical imaging, showing that with the aid of a NaI(Tl) or a CsI(Tl) scintillator the device response is linearly dependent on the x-ray dose rate. 43 This material has also been shown to be sensitive to 6 MV x rays via indirect detection (Gd 2 O 2 S:Tb phosphor material) with stable performance (2% loss in photocurrent) up to 360 Gy, 44 suggesting its longevity for applications in ionizing radiation environments.…”
Section: Introductionmentioning
confidence: 99%
“…From the point view of space applications, a good benchmark for OPV is a PCE of 12-15% to compete with other technologies, which is also aligned with the prediction of OPV efficiency limit. 3 We have investigated earlier 5,6 the reason for degradation of polymer solar cells when subjected to X-ray radiation. It was found that no significant changes took place in the polymer structure; the morphology and crystallinity of the photoactive layer are retained after radiation.…”
mentioning
confidence: 99%
“…We systematically study the effect of X-ray irradiation on five different polymer/cathode interfaces. We fix the polymer active layer to the work horse poly(3hexylthiophene) (P3HT): [6,6]-phenyl-C61-butyric acid methyl ester (PCBM) system and vary the cathode to Al, Ca/Al, LiF/Al, TiO 2 :Cs/ Al and ZnO/Al interface to reveal the underlying phenomenon.…”
mentioning
confidence: 99%